Testing Normality for Daily Returns from the Nepalese Stock Market - Rashesh Vaidya; Dilli Raj Sharma; Jeetendra Dangol (Journal of Business and Management Review, 2022)
Researchers and investors are interested in the normality of the return from the stock market and the establishment of the Efficient Market Hypothesis (EMH). Nevertheless, a statistical distribution of the normality of the return helps investors predict the stock market return with the help of the basic mean and standard deviation values of the return. Hence, the paper tested the normality of the daily returns from the Nepalese stock market, Nepal Stock Exchange Limited (NEPSE). The paper followed the statistical results and data visualization to determine the normality of the stock market return. The data visualization and statistical results have shown that the daily return from the NEPSE follows a normal distribution. The test statistics for the normality of the data also show a normal distribution for the NEPSE daily return. Similarly, the parameters for the fitted distribution also reflect normality. The daily transaction volume at the stock market normally leads the daily stock market return in normality as well. The fitting of a normal distribution for the daily returns reflects that the Nepalese investors could predict market risk and return using two statistical parameters, i.e., standard deviation and mean, respectively.